Phytopharmaceutical Interventions in Neurodegenerative Disorders: Emerging Trends and Prospects - Spandana, CH V L D; K N, Anitha; Muddagoni, Jyothi; Gawai, Nitin Motiram; Chauhan, Vishal; Sawarkar, Hemant A.; Landge, Amol Dagdu; Devhare, Lalchand (Journal of Neonatal Surgery, 2025)
Neurodegenerative diseases, characterized by progressive neuronal loss and dysfunction, pose significant challenges to global health. Recent advances in phytopharmaceuticals have emerged as a promising avenue for the prevention and treatment of these disorders. This review explores the current research on various plant-derived compounds, highlighting their neuroprotective effects and mechanism of action, including antioxidant, anti-inflammatory, and neurotropihic activities. We discuss specific phytochemicals such as flavonoids, phenolic acids, and alkaloids that have demonstrated efficacy in preclinical and clinical studies for conditions like Alzheimer’s, Parkinson’s, and Hungtington’s diseases. Additionally, the integration of modern approaches such as network pharmacology and herbal-based nanosystems is examined for enhancing the bioavailability and therapeutic potential of these natural products. Despite the promising findings, challenges such as limited bioavailability and standardization of herbal formulations remain. Future directions in research should focus elucidating the molecular mechanisms underlying the neuroprotective effects of phytochemicals, conducting rigorous clinical trials, and developing innovative delivery systems to optimize their therapeutic applications. By bridging traditional knowledge with contemporary scientific methodologies, phytopharmaceuticals hold the potential to significantly improve treatment outcomes for patients suffering from neurodegenerative diseases.